Targeted therapy with a localised abluminal groove, low-dose sirolimus-eluting, biodegradable polymer coronary stent (TARGET All Comers): a multicentre, open-label, randomised non-inferiority trial. Issue 10153 (29th September 2018) - Lansky, Alexandra; Wijns, William; Xu, Bo; Kelbæk, Henning; van Royen, Niels; Zheng, Ming; Morel, Marie-angèle; Knaapen, Paul; Slagboom, Ton; Johnson, Thomas W; Vlachojannis, Georgios; Arkenbout, Karin E; et al.
Summary: Background: The FIREHAWK is a drug-eluting stent with a fully biodegradable sirolimus-containing polymer coating localised to recessed abluminal grooves on the stent surface. We investigated clinical outcomes with this targeted, low-dose, biodegradable polymer, sirolimus-eluting stent compared with XIENCE durable polymer, everolimus-eluting stents in an all-comers population. Methods: The TARGET All Comers study was a prospective, multicentre, open-label randomised non-inferiority trial done at 21 centres in ten European countries. Patients with symptomatic or asymptomatic coronary artery disease and objective evidence of myocardial ischaemia who qualified for percutaneous coronary intervention were randomised 1:1 to undergo implantation of a FIREHAWK or XIENCE. Randomisation was web-based, with random block allocation and stratification by centre and ST elevation myocardial infarction. Outcome assessors were masked to treatment allocation, but treating physicians and patients were not. The primary endpoint was target lesion failure at 12 months, a composite of cardiac death, target vessel myocardial infarction, or ischaemia-driven target lesion revascularisation. The control event rate for XIENCE was assumed to be 7%, the non-inferiority margin was 3.5%, and the primary analysis was in the intention-to-treat population, censoring patients who did not have either an event before 365 days or contact beyond 365 days. Late lumen loss was the primary endpoint of an angiographic substudy designed to investigate the non-inferiority of the FIREHAWK compared with the XIENCE stent. This trial is registered withClinicalTrials.gov, numberNCT02520180 . Findings: From Dec 17, 2015, to Oct 14, 2016, 1653 patients were randomly assigned to implantation of the FIREHAWK (n=823) or XIENCE (n=830). 65 patients in the FIREHAWK group and 66 in the XIENCE group had insufficient follow-up data and were excluded from the analyses. At 12 months, target lesion failure occurred in 46 (6·1%) of 758 patients in the FIREHAWK group and in 45 (5·9%) of 764 patients in the XIENCE group (difference 0·2%, 90% CI −1·9 to 2·2, pnon-inferiority =0·004, 95% CI −2·2 to 2·6, psuperiority =0·88). There were no differences in ischaemia-driven revascularisation or stent thrombosis rates at 12 months. 176 patients were included in the angiographic substudy, in which in-stent late lumen loss was 0·17 mm (SD 0·48) in the FIREHAWK group and 0·11 mm (0·52) in the XIENCE group (p=0·48), with an absolute difference of 0·05 mm (95% CI −0·09 to 0·18, pnon-inferiority =0·024). Interpretation: In a broad all-comers population of patients requiring stent implantation for myocardial ischaemia, the FIREHAWK was non-inferior to the XIENCE as assessed with the primary endpoint of target lesion failure at 12 months and in-stent late lumen loss at 13 months. The FIREHAWK is a safe and effective alternative stent to treat patients with ischaemic coronary artery disease in clinical practice. Funding: Shanghai Microport Medical.